(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
The role of cultural absorption in the process of language learning is incomparable. The language is studied not only by a set of words and grammatical rules, but also by it the worldview, values, customs and historical experiences of a particular people. Culture as an integral part of language allows language learners to gain a deeper understanding of language, applying it naturally and effectively. Therefore, the process of cultural absorption in language learning requires a broader and more meaningful approach to language than just technical learning.